Riverine microplastics and their interaction with freshwater fish - Badiozaman Sulaiman; Jamie C. Woodward; Holly A. Shiels (Water Biology and Security, 2023)
This paper outlines the nature of microplastic contamination in rivers and the risks to freshwater fishes. We discuss how input sources influence the concentration and composition of microplastics and examine factors that subsequently influence their spatiotemporal dynamics in a river system. We then discuss how the distributions and assemblages of microplastics can impact the risk of interactions with fishes, and the processes associated with the internalisation of microplastic into the body and across the organs and tissues. Finally, we examine the physical and toxicological effects of microplastic exposure in fish species, with special attention directed towards impacts at environmentally relevant concentrations. This review integrates expertise in fluvial geomorphological processes and how they influence the movement and storage of microplastics in river channel environments at a range of scales. We combine this knowledge with expertise in fish ecology and biology to set out a new and integrated analysis of microplastic dynamics in rivers and how these microplastics interact with fish. The integration of knowledge from these fields allows us also to comment upon the microplastic risk to fish and other biota in river environments.